The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/ijms22116006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Details of the Frataxin–Scaffold Interaction during Mitochondrial Fe–S Cluster Assembly

Abstract: Iron–sulfur clusters are essential to almost every life form and utilized for their unique structural and redox-targeted activities within cells during many cellular pathways. Although there are three different Fe–S cluster assembly pathways in prokaryotes (the NIF, SUF and ISC pathways) and two in eukaryotes (CIA and ISC pathways), the iron–sulfur cluster (ISC) pathway serves as the central mechanism for providing 2Fe–2S clusters, directly and indirectly, throughout the entire cell in eukaryotes. Proteins cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 91 publications
(188 reference statements)
1
5
0
Order By: Relevance
“…Unfortunately, a high-resolution structure of the human mature FXN 81–210 oligomer is still lacking. Many studies reported iron-binding properties of monomeric frataxin proteins ( Campbell et al, 2021 ). A total of twelve aspartate and glutamate residues along the conserved acidic ridge were found to bind iron but no structurally defined iron-binding site could be identified.…”
Section: Iron Storage Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, a high-resolution structure of the human mature FXN 81–210 oligomer is still lacking. Many studies reported iron-binding properties of monomeric frataxin proteins ( Campbell et al, 2021 ). A total of twelve aspartate and glutamate residues along the conserved acidic ridge were found to bind iron but no structurally defined iron-binding site could be identified.…”
Section: Iron Storage Functionmentioning
confidence: 99%
“…First, the number of iron bound to frataxin varied between studies (from one to seven), with Fe 2+ and Fe 3+ binding with similar affinities. The proposed iron-binding site involves several glutamate and aspartate residues from the conserved acidic ridge ( Campbell et al, 2021 ). However, the structure of the complex between FXN and the NFS1-ISD11-ACP-ISCU complex ( Fox et al, 2019 ) revealed that most of these amino acids are either directly involved in the interaction with NFS1 or in the internal structure of the protein ( Figure 3 ).…”
Section: Specialized Role Of Frataxin In Iron-sulfur Cluster Biosynth...mentioning
confidence: 99%
“…A set of additional proteins ensures the proper functioning of SDH. These proteins encompass those involved in the assembly of iron-sulfur clusters, such as Frataxin [ 58 ]. The deficiency of Frataxin is known to cause Friedreich’s ataxia.…”
Section: The Succinate Crossroad: Enzymes and Metabolites Stakeholdersmentioning
confidence: 99%
“…The activity of a set of additional proteins ensures the proper functioning of SDH. These proteins encompass those involved in the assembly of iron-sulfur clusters, such as Frataxin [58]. The deficiency of Frataxin is known to cause Friedreich's ataxia.…”
Section: Figure 1 the Succinate Dehydrogenase (A) And Some Of Its Inh...mentioning
confidence: 99%